2005
DOI: 10.1007/s00213-005-0242-x
|View full text |Cite
|
Sign up to set email alerts
|

Some facilitatory effects of lorazepam on dynamic visual binding

Abstract: Rationale: The benzodiazepine, lorazepam enhances the potential for inhibitory GABA A (-aminobutyric acid) synapses in the cortex to stabilize postsynaptic, excitatory activity by synchronizing discharge rates at frequencies of around 40 Hz. Treatment with lorazepam also affects contour integration processes, suggesting GABA A -mediated synchronization plays a role in visuo-spatial organization. This conclusion is supported by other physiological studies that link visual feature integration with neuronal sync… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…The elevated RTs to triangle targets may reflect the greater number of display locations (six, as opposed to four each in the square and hexagon matrices), even though in two of these locations a target was never presented. In agreement with the previous pattern of effects reported with this paradigm (i.e., Becker, Elliott, & Lachmann, 2005;Elliott, Becker, Boucart, & Müller, 2000;Elliott et al, 2006;Elliott, Herrmann, Mecklinger, & Müller, 2000;Elliott & Müller, 1998, 2000, the target prime interaction was found to be significant [F(1,13) 23, p .01], describing significant priming effects (i.e., the mean difference interphase minus intraphase premask RTs) that were confined to target trials (the mean priming effect in target-present conditions [and standard error of the mean] was 29 [4] msec, as compared with 6 [4] msec on targetabsent trials). On this basis and with a view to examining the priming effects specifically, further analyses were conducted on the target-present data only.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The elevated RTs to triangle targets may reflect the greater number of display locations (six, as opposed to four each in the square and hexagon matrices), even though in two of these locations a target was never presented. In agreement with the previous pattern of effects reported with this paradigm (i.e., Becker, Elliott, & Lachmann, 2005;Elliott, Becker, Boucart, & Müller, 2000;Elliott et al, 2006;Elliott, Herrmann, Mecklinger, & Müller, 2000;Elliott & Müller, 1998, 2000, the target prime interaction was found to be significant [F(1,13) 23, p .01], describing significant priming effects (i.e., the mean difference interphase minus intraphase premask RTs) that were confined to target trials (the mean priming effect in target-present conditions [and standard error of the mean] was 29 [4] msec, as compared with 6 [4] msec on targetabsent trials). On this basis and with a view to examining the priming effects specifically, further analyses were conducted on the target-present data only.…”
Section: Resultssupporting
confidence: 92%
“…Although the paradigm of Elliott and Müller offers a basis for analysis of the dynamic system underlying figural prime formation, the data thus far refer to primes and targets in square arrangement and, as a consequence, offer no indication of potential interactions either of stimulus form or complexity or of the effects of more than one possible target upon the efficiency of oscillatory priming. Recent evidence has shown that the primes do include information about the spatial relations between the premask crosses, evidence which clearly suggests the prime to be a form of Gestalt-related grouping (Elliott, Giersch, & Seifert, 2006). With this in mind, the main goals of the research presented here were to explore whether or not variations in priming performance might be explained by means of variations in figural complexity and, on this basis, whether evidence exists to support the idea of neuronal synchronization as one measure of the minimum principle.…”
mentioning
confidence: 99%
“…A model by Jeffreys, Traub and Whittington (1996) demonstrated that embedding an isolated interneuron in a network of cells coupled by GABA a -mediated inhibitory postsynaptic potentials would cause it to oscillate at 33-Hz (see Elliott, Giersch & Seifert, 2006 for evidence of involvement of GABA a in the modulation of visual gamma-band oscillations). Palva et al (2002) used MEG to investigate the eGBR evoked by speech and non-speech sounds.…”
mentioning
confidence: 99%
“…Evidence of priming is typically indicated by significant Target × Prime interaction in the analysis of variance (ANOVA see all experiments reported in Elliott and Müller, 1998, 2000, 2001; Elliott et al, 2000; Conci et al, 2004; Becker et al, 2005; Elliott et al, 2006a; Shi and Elliott, 2007). Resolution of this interaction always refers to a target-specific RT advantage for the intra- vs. interphase premask conditions.…”
Section: Results Of Studymentioning
confidence: 99%